THE PRINCIPLES OF QARD HASAN IN DEBTS AND RECEIVABLES: (OF STRENGTHENING THE UMMAH ECONOMY AND SHARIA FINTECH REGULATION) - Hafidzi, Anwar; Nasrullah, Nasrullah; Yusuf, Mahmud (STIT Ibnu Rusyd Tanah Grogot, 2025)
The principles of Qard Hasan and Ihsan in Islamic debt practices have great potential in strengthening the people's economy through an Islamic financial approach that is equitable and based on spiritual values. However, the integration of these principles in the regulation and practice of Islamic fintech in Indonesia still faces challenges, both in terms of policy, public awareness, and the sustainability of the business model. This study aims to analyze the role and implementation of the principles of Qard Hasan and Ihsan as reflected in QS. Al-Baqarah: 280-281, and evaluate its contribution to strengthening the digital Islamic financial system in Indonesia. The method used is Systematic Literature Review (SLR) with PRISMA approach through five scientific databases: Crossref, ScienceDirect, Semantic Scholar, SINTA, and Google Scholar. The results showed that Qard Hasan has a strategic role in encouraging financial inclusion and empowering MSMEs without usury. While the value of Ihsan strengthens the dimensions of ethics and social justice in economic interactions. In the context of Islamic fintech, the integration of Qard Hasan still requires the support of clear regulations, adaptive technology, and massive public education. This research recommends the development of Qard Hasan-based Islamic Fintech model as an ethical and inclusive financing solution based on maqashid sharia.